2010
DOI: 10.5194/acp-10-10237-2010
|View full text |Cite
|
Sign up to set email alerts
|

Emission and dry deposition of accumulation mode particles in the Amazon Basin

Abstract: Abstract. Size-resolved vertical aerosol number fluxes of particles in the diameter range 0.25-2.5 µm were measured with the eddy covariance method from a 53 m high tower over the Amazon rain forest, 60 km NNW of Manaus, Brazil. This study focuses on data measured during the relatively clean wet season, but a shorter measurement period from the more polluted dry season is used as a comparison. Size-resolved net particle fluxes of the five lowest size bins, representing 0.25-0.45 µm in diameter, were in general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 57 publications
(69 reference statements)
1
34
0
Order By: Relevance
“…Lamaud et al (1994) found that particle deposition velocity (V d ) is related to friction velocity (u * ) and atmospheric stability. This was also supported by the studies of Grönholm et al (2007), Pryor (2006), Pryor et al (2007), and Ahlm et al (2009Ahlm et al ( , 2010. Many studies found fluxes were often upward (negative "deposition"), with frequency ranging from near 20 % to over 40 % (Pryor et al, 2008c) of the total number of flux measurements.…”
Section: Introductionsupporting
confidence: 48%
See 2 more Smart Citations
“…Lamaud et al (1994) found that particle deposition velocity (V d ) is related to friction velocity (u * ) and atmospheric stability. This was also supported by the studies of Grönholm et al (2007), Pryor (2006), Pryor et al (2007), and Ahlm et al (2009Ahlm et al ( , 2010. Many studies found fluxes were often upward (negative "deposition"), with frequency ranging from near 20 % to over 40 % (Pryor et al, 2008c) of the total number of flux measurements.…”
Section: Introductionsupporting
confidence: 48%
“…Forest types and locations include: mixed deciduous in eastern Tennessee (Hicks et al, 1989) and southern Indiana, USA (Pryor et al, 2009); pine in Hyytiälä, Finland (e.g. Buzorius et al, 1998;Grönholm et al, 2007); maritime pine in Les Landes, France (Lamaud et al, 1994); douglas fir in Northern Holland (Gallagher et al, 1997); spruce in Germany, at Solling (Bleyl, 2001) and near Münchberg (Held and Klemm, 2006); beech in Soro, Denmark (Pryor, 2006); and Amazonian rain forest near Manaus, Brazil (Ahlm et al, 2010). The majority of these studies measured aerosol fluxes using the eddy covariance (EC) technique with Condensational Particle Counters (CPCs), which measure the total particle number concentration over a particle size range typically between 10 nm and 1 µm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, only a few attempts were made to directly measure the flux of bacteria from plant canopies (Lindemann et al, 1982;Lindemann and Upper, 1985;Lighthart and Shaffer, 1994;Crawford et al, 2014). Direct eddy covariance measurements of aerosol exchange in tropical forests, where PBAs represent a significant fraction of the airborne particulate matter (Graham et al, 2003), were also performed by Ahlm et al (2010) and , potentially giving a proxy for microbial emission in tropical ecosystems. The mass of PBAs that is actually released by different land use types under different conditions and, more importantly, the specific composition of such fluxes and their quantification remains so far mostly unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Particle number fluxes over the tropical forest typically correspond to net deposition, with potential forest sources of PBAP in the coarse mode (>1 μm) just after sunrise (Ahlm et al 2009;Ahlm et al 2010;Rizzo et al 2010). The observation of net deposition of NR-PM 1 aerosol mass with an exchange velocity of −0.1 mm s −1 is consistent with particle number flux measurements at a nearby tower site with a modal exchange velocity of −0.3 mm s −1 (Ahlm et al 2009) (see the online supplemental information for comparison of particle number versus mass fluxes).…”
Section: Amaze-08 Diel Patternsmentioning
confidence: 99%